Investigating Discursive Interactions in Science Lessons: “contextual lenses” on Research in Science Education (Revista Brasileira de Pesquisa em Educação em Ciências, 2018)
We present a critical discussion about context as a theoretical-methodological construct in research that investigates discursive interactions during science lessons. Based on the notion that context is historical, multiple and interactive, we understand that research can focus on different levels of context. We used a wide range of papers about elementary school, selecting eight examples considered illustrative to ground our discussion. Developing “contextual lenses” we characterize the diverse ways to consider context, from the more local level (instructional and classroom), to a broader level (institutional, community, social and cultural). We point the potential of a more descriptive focus in science education research to emphasize contexts that go beyond the instructional.